Introduction to Interactive Video-Based E-Learning to Improve Critical Thinking Skills in Vocational High School Students - Irwan, Irwan (Pascasarjana Universitas Mataram, 2024)
This Community Service (PKM) activity aims to introduce interactive video-based e-learning to improve critical thinking skills in Vocational High School (SMK) students. Critical thinking skills are essential in facing the challenges of the world of work, especially for vocational school graduates. This activity was conducted online through the Zoom application, involving vocational school teachers as the main participants. The training focuses on using interactive videos as a learning medium that integrates interactive elements such as reflective questions, simulations, and problem-solving tasks to stimulate active student engagement. The evaluation was carried out through pre-test and post-test tests that showed a significant improvement in students' critical thinking skills, with an average post-test score of 80, an increase from 65 in the pre-test. In addition, a survey of teachers showed that 85% of participants benefited from using interactive videos to make learning more engaging and effective. However, some challenges related to internet infrastructure and students' technical ability to access video were identified. As a solution, materials are also provided offline. The results of this activity show that interactive video-based e-learning effectively improves the critical thinking skills of vocational school students. Hopefully, this method can be adapted more widely in the context of vocational education and contribute to developing the quality of education in Indonesia.